Definición de las condiciones de operación para la producción de larva de mosca soldado negra (Hermetia Illucens). (2022)
The following document focused on defining the operating conditions for the production of black soldier fly larvae (Hermetia illucens). Larvae were fed with organic residues of pre-consumer foods obtained from the Secretariat of Social Integration of Bogotá and residues obtained from the brewing industry, at different proportions which guarantee different carbon/nitrogen ratios, in a system controlling the temperature and relative humidity of the air. Operating ranges, incubation system, hatching technique, counting technique and initiation substrate were defined. For the culture system, the construction of the bioreactor was explained, which has a temperature and relative humidity control system, larval density, C/N ratio and substrate conditioning.